Praktik Konversi Utang Menjadi Saham Sebagai Penerapan Prinsip Business Going Concern dalam Kepailitan dan PKPU - Jonathan Fide Mulya; Lastuti Abubakar; Anita Afriana (Dinasti Review Publisher, 2024)
The research was conducted with the aim of knowing and explaining the implementation of business going concern through the conversion of debt into shares (debt to equity swap) in PKPU in order to achieve peace between debtors and creditors. The research was carried out by providing understanding to legal practitioners, entrepreneurs, the government and readers that debtors who experience problems paying debts to two or more creditors can submit a PKPU application to prevent the debtor from being threatened with bankruptcy. The research carried out uses a normative juridical approach which includes research on library materials or secondary materials which includes research on the application of legal principles and norms to produce arguments, theories and inventions for resolving legal problems in implementing business going concern principles through converting debt into shares. (debt to equity swap) in the PKPU process by reviewing the Bankruptcy and PKPU Law (UUKPKPU). The research results show that the conversion of debt into shares (debt to equity swap) is part of debt restructuring in order to provide justice for creditors and debtors by achieving peace at PKPU.